Changes of components and chemical structure of bitumen-derived liquids during retorting Indonesian oil sands. Issue 13 (2nd July 2016) - Han, Xiangxin; Chen, Bin; Jiang, Xiumin
ABSTRACT: It is very important to explore the changes of components and chemical structure of bitumen-derived liquids during retorting oil sands. In order to reveal that, this work prepared natural bitumen and pyrolytic oil samples by the extraction and the retorting of Indonesian oil sands, respectively, and employed GC-MS (gas chromatograph-mass spectrometer) and 13 C NMR (nuclear magnetic resonance) to analyze them. Due to the thermal decomposition of organic macromolecules of natural bitumen, the yield of pyrolytic oil from the retorting is only 62.86 63.05% on the basis of the amount of the extracted natural bitumen, among which the content of low-molecular-weight compounds (C7–C10) increases largely from 25.59% to above 50%. Further increase of the retorting temperature from 450°C to 520°C slightly increases the oil yield. 13 C NMR analysis was used to compare the organic carbon structure characteristics between natural bitumen and pyrolytic oil. Obvious changes in both methylene chain length and aliphatic methyl content also support the intense thermal cracking of organic carbon components during the retorting of oil sands.